Clinical symptoms and volumetric radiological responses of acoustic neuroma patients, treated with hypo-fractionated image guided radiotherapy (IGRT) at Groote Schuur hospital between 2013 and 2016 - Riddick, Alison (Division of Radiology, 2019)
Background: Stereotactic radiosurgery (SRS) is the gold standard for treatment of small and medium sized tumours, although fractionated regimens are well described. Access is limited in resource-constrained settings. There are no South African data describing outcomes of AN patients treated with fractionated stereotactic radiotherapy (SRT) using photons. We describe clinical and radiological outcomes of AN patients treated with SRT at an academic centre in Cape Town, South Africa. Objectives: To describe patient demographics, tumour characteristics and patients’ symptoms and changes in symptoms at follow-up. To investigate tumour local control (LC) rates at last follow up MRI, and compare LC rates described for SRS in the literature. To correlate radiologists’ serial 2D maximum linear diameter (MLD) measurements with calculated 3D tumour volume (TV). Methods: Fifteen AN patients treated with modified SRT (18.0gy/3fractions, were identified from the planning database; 13 were included. Patient data and tumour characteristics (size, laterality and previous surgery) were retrospectively extracted from clinic folders. Initial planning data was accessed and checked. Tumour volumes were contoured by the author on all subsequent MRI’s per patient and validated by a second investigator; tumour volume (TV) was automatically calculated. Radiologist’s 2D MLDs were compared with 3D TV. Sensitivity and specificity of radiologist reported change of MLD as a measure of actual change in TV was calculated. LC was calculated, from time of treatment to time of last MRI or time of progression (defined as ≥20% increase in TV). Results: Mean age was 60.4years (range 45-79years), with 4 (30.8%) being female. Seven patients (53.8%) had left sided tumours and median tumour size was 1.15cm3 (mean 1.59 cm3; range 0.62-3.35 cm3). Nine patients (69.2%) had Koos stage 2 ANs, 3 (23.1%) had stage 3 tumours and 1 (7.7%) had a stage I tumour. Two patients had NF2.Median follow-up time 12 was 29 months (range 0-50 months). Median baseline TV, as was 1.15 cm3 (mean 1.59cm3 with range 0.62-3.35 cm3). Three patients had no follow-up MRIs: 2 demised and 1 declined further follow-up. In total 5 patients died, 4 of unrelated causes and 1 of unknown cause (median time to death after RT 24 months, range 6 - 36 months). LC was 74% at 36months. Hearing preservation rate was 67%. No new facial or trigeminal nerve symptoms were noted. Radiologists correctly reported tumour growth in 100% of tumours that grew, and specificity was 77.3% in those that were stable. Conclusion: This is the first local study in hypofractionated SRT using photons. We show lower LC rates than seen in literature; our numbers are small and short follow up time short, with high attrition rates. Acute treatment toxicities were absent. Longer term follow-up is needed to assess late RT effects. A prospective study using this method of treatment would better define LC.